فعالیة حاضنات الاعمال في خلق القدرة التنافسیة للمؤسسة الجزائریة - عبد الوهاب معمري; نبیلة مكي; شفیقة بلمیر (Finance and Business Economies Review, 2017)
The various developed and developing countries seek to rehabilitate their institutions in order to overcome all the obstacles that would stand in front of the continuation and growth of these institutions, and help them overcome the burdens of the start-up phase, the completion of their projects, the efficiency of production and the satisfaction of the needs of the market And to create them in order to compete in any market. For this reason, the problem was raised by the effectiveness of business incubators (facilitation center and institutional incubator) in creating the competitiveness of economic institutions in Algeria? The descriptive approach presented the theoretical aspects of the subject variables. The analytical and statistical approach helped us in analyzing the opinions of the respondents in the sample of the study of 100 institutions on the possibility of institutional incubators in creating the competitiveness of the economic institution in Algeria to ensure in the results that there is a statistically significant relation Between institutional nurseries and facilitation centers in their support of enterprise competitiveness.